1976
DOI: 10.1190/1.1486616
|View full text |Cite
|
Sign up to set email alerts
|

Reply to J. W. Adams by R. N. McDonough.

Abstract: Adams correctly points out a blunder of mine, in that the spatial correlations [Formula: see text] in my equation (75) should be identified with the correlations [Formula: see text] in equation (32), and not with the data samples [Formula: see text] in equation (11). In effect, the averaging in equation (67) replaces the averaging in equation (12). In the case of nonuniform array spacing, the necessary interpolation can still be done in [Formula: see text], as I suggest, but one might also interpolate directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…3, step 4). It has been shown by isotopic labeling that the inversion of configuration at the 3 position of the pentose involves a two-base mechanism, because the hydrogen at position 3 of the product, xylulose-5-P, is derived from water (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…3, step 4). It has been shown by isotopic labeling that the inversion of configuration at the 3 position of the pentose involves a two-base mechanism, because the hydrogen at position 3 of the product, xylulose-5-P, is derived from water (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Further, she found that TBLT improved students' self-esteem, creativity, social skills, and personal relations. McDonough and Chaikitmongkol (2007) piloted a TBLT course with learning strategy training modules in a Thai University and found that the learners not only enjoyed the course, but also were becoming more independent learners. Demir (2008) found that the implementation of 10 reading tasks in two preparatory reading classes at a university in Turkey resulted in learners developing the skills of learning on their own and becoming autonomous in the reading process.…”
Section: Tblt In Classroomsmentioning
confidence: 99%
“…This enzyme, which equilibrates ~-ribulose-5-P and ~-xylulose-5-P, has been obtained from several bacterial sources (60,61), the enzyme from Aerobacter aerogenes having been studied extensively (62)(63)(64)(65). Neither hydrogen nor oxygen from water is found in the sugar (62), implying a mechanism like that of UDP-glucose-4 ' -epimerase in which NAD accepts the substrate hydrogen without exchange with the medium.…”
Section: Dtdp-l-rhamnose Synthetase Gdp-l-fucose Synthetasementioning
confidence: 99%
“…T h e enzyme has been purified from microbial sources (62,73). Unlike the Lribulose-5-P-4-epimerase reaction, the C-3 hydrogen exchanges with the medium during the reaction (62,73), and use of [32H]-~-xylulose-5-P as substrate decreases the reaction velocity by a factor of 2 to 3 (3).…”
Section: ~-Ribulose-5-p-3-epimerasementioning
confidence: 99%
See 1 more Smart Citation